PS1:13 Systemic lupus erithematosus with positive anticentromere antibodies – a different clinical subgroup?. (21st March 2018) - Caetano, J; Favas, C; Amaral, M; Oliveira, S; Alves, JD
Abstract : Introduction: Anticentromere antibodies (ACA) are one of the most specific systemic sclerosis (SSc)-related antibodies. The presence of ACA has also been identified in other autoimmune diseases, mainly in SSc overlap syndromes with Sjogren syndrome (SjS), primary biliary cirrhosis and rarely in patients with systemic lupus erythematosus (SLE). Purpose: To evaluate the prevalence and clinical significance of ACA in a cohort of SLE patients. Methods: Retrospective analysis of all ACA positive SLE patients (ACA +SLE), from a cohort of 270 consecutive SLE patients fulfilling the 2012 SLICC Criteria and/or 1997 ACR Criteria, of a single referral centre, between 2010–2016. Comparative analysis was made with a representative group of 63 consecutive SLE patients without ACA (ACA-veSLE). Data were obtained by medical records review. Results: From 270 SLE patients, 10 (3.7%) were ACA+. All ACA +SLE patients were female. The age at the time of diagnosis was not different between the groups (40.9±16.6 years ACA +SLE vs 37.8±16.2 years ACA-veSLE), but ACA +SLE patients had longer disease duration (15.2±17.3 years vs 9.5±8.8 years, p=0.002, respectively). ACA +SLE patients had significantly more Raynaud's phenomenon (RP) (p=0.028), but none had a capillaroscopy SSc pattern. Sicca symptoms were also more frequent in ACA +SLE (p=0.013), with only 1 patient with a positive anti-SSA antibody. None of these patients fulfilled criteria for SjS. Prevalence of arthritis, oral ulcers, alopecia, cutaneous lupus, serositis, neurologic, renal and hematologic involvement was not significantly different between the two groups. Hypocomplementemia at any time of the disease course was more frequent in ACA-veSLE (p=0.016). Antiphospholipid antibodies were less frequently positive in ACA+SLE patients (20% vs 46%, p=0.1), and none fulfilled criteria for antiphospholipid syndrome (APS) (21% of ACA-veSLE patients with APS). Apart from RP, SSc-associated clinical characteristics (skin thickening, digital ulcers, telangiectasia, pulmonary arterial hypertension, interstitial lung disease, gastroesophageal reflux and calcinosis) were not present in any of the ACA+SLE patients. Conclusions: ACA +SLE patients do not constitute a different clinical subgroup regarding organ involvement, but can associate with a lower probability of concomitant APS. Moreover, although highly specific of SSc, ACA can be identified in SLE patients without SSc overlap, and should not hamper the diagnosis of SLE.